1,6-Conjugate-addition-induced [2+1] annulation of para-quinone methides and pyrazolones: synthesis of bis-spiro compounds with contiguous quaternary spiro-centers - Kale, Someshwar B.; Jori, Popat K.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (Organic Letters, 2019)
A diastereoselective formal 1,6-conjugate-addition-mediated [2 + 1] annulation reaction using p-quinone methides and pyrazolones has been described. The corresponding bis-spiro[cyclohexadienone-cyclopropane-pyrazolone] compounds were obtained in very good yield under mild reaction conditions.

Transition-metal-free glucose-derived carbonaceous catalyst catalyzes direct C-H arylation of unactivated arenes with aryl halides - Jori, Popat K.; Jadhav, Vrushali H. (ChemistrySelect, 2019)
Transition metal free coupling reactions have gained lot of importance recently. The traditional method for the synthesis of biaryl's uses organometallic reagents for the arylation reactions. There are certain drawbacks associated with such traditional methods. Use of expensive metals, metal impurities in the products formed and disposal of metal waste generated are major problems that need to be taken care of. Thus, research has been focussed on using transition metal free catalyst for cross coupling reactions to encourage green environment and it still remains a challenge for researchers. Carbonaceous catalyst have attracted great attention recently as a heterogeneous catalyst as it has a carbon skeleton that is stable, easily separable, reusable, eco-friendly and highly economical compared to other heterogeneous catalyst. Carbonaceous catalysts have been studied in variety of organic reactions such as hydrolysis, dehydration, esterification, alkylation, condensation, oxathioketalization, dimerization, benzylation and trimethylsilylation, etc. It was estimated that - stacking interactions between carbonaceous catalyst and arenes will accelerate the coupling reaction. However to the best of our knowledge, there are no reports available in literature on use of carbonaceous catalyst for direct arylation of arenes. And thus, we developed a new method for C-H arylation of unactivated arenes with aryl halides using a transition metal free D-glucose derived carbonaceous catalyst.
Keywords: Arylation; carbonaceous; glucose; metal-free

Efficient synthesis of gamma-valerolactone-a potential fuel from biomass derived levulinic acid using catalytic transfer hydrogenation over Hf@CCSO3H catalyst - Jori, Popat K.; Jadhav, Vrushali H. (Catalysis Letters, 2020)
A new hafnium based carbonaceous catalyst (Hf@CCSO3H) was prepared by simultaneous carbonization and sulfonation of readily available glucose, followed by incorporation of hafnium metal on the surface of catalyst. The catalyst was well characterized using FT-IR, PXRD, EDX, SEM, C-13 CPNMR, XPS and BET analysis. The catalytic activity of Hf@CCSO3H was evaluated for synthesis of gamma-valerolactone-a potential fuel and green solvent. gamma-valerolactone was synthesized from biomass derived levulinic acid by catalytic transfer hydrogenation using 150 wt% of catalyst at 200 celcius for 24 h in isopropanol solvent as a hydrogen donor. 100% conversion of levulinic acid was achieved with an excellent yield of 96% with more than 99% selectivity of gamma-valerolactone as evident from GC analysis. The method developed is simple, efficient and economical. [GRAPHICS] .
Keywords: gamma-Valerolactone; Hydrogenation; levulinic acid; Transfer

Highly efficient zirconium based carbonaceous solid acid catalyst for selective synthesis of 5-HMF from fructose and glucose in isopropanol as a solvent - Jori, Popat K.; Jadhav, Vrushali H. (Catalysis Letters, 2022)
A new zirconium based carbonaceous solid acid catalyst Zr@CC-PA with both Lewis and Bronsted acidic sites was prepared by simultaneous carbonization and phosphonation of glucose followed by incorporation of zirconium metal on the surface of the catalyst. The catalyst was easy to prepare and the synthesized catalyst was well characterized using different techniques such as FT-IR, P-XRD, EDAX, SEM, TEM and XPS analysis. The catalytic activity was evaluated for synthesis of a very important platform chemical 5-HMF from fructose to glucose using isopropanol as a solvent. The catalyst was found to be highly efficient giving 86% yield of 5-HMF from fructose and 45% yield from glucose with high selectively. The catalyst can be reused at least four times without depreciation in its catalytic activity. The catalytic method developed is efficient, green and economical.
Keywords: 5-Hydroxymethylfurfural; fructose; glucose; Zirconium based

Rongalite as a sulfone source: sulfonylation of para-quinone methides and alkyl/allyl halides - Kale, Someshwar B.; Jori, Popat K.; Das, Utpal (Chemistry-an Asian Journal, 2022)
A one-pot three-component reaction using p-quinone methides, rongalite and alkyl/allyl halides has been described. The corresponding unsymmetrical sulfones were obtained in good yields under mild reaction conditions in the absence of any metal, base or any other additive.
Keywords: Alkyl halides; diaryl methine; p-Quinone methide; rongalite; sulfonylation